2015
DOI: 10.1016/j.addbeh.2014.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized smokers' expectancies for electronic cigarettes versus tobacco cigarettes

Abstract: Introduction To compare hospitalized smokers’ expectancies for electronic cigarettes (e-cigarettes) against their expectancies for tobacco cigarettes and evaluate relationships between e-cigarette expectancies and intention to use e-cigarettes. Methods Analysis of baseline data from a one-year longitudinal observational study. The setting was a tertiary care academic center hospital in the Southeastern U.S. Participants were 958 hospitalized tobacco cigarette smokers. A questionnaire of e-cigarette expectanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(60 citation statements)
references
References 40 publications
1
58
1
Order By: Relevance
“…Hospitalised tobacco smokers expect fewer negative and positive outcomes from e-cigs versus conventional cigarettes, which suggests that e-cigs might be a viable, though imperfect, substitute to conventional cigarettes. 38 Vapers stated that e-cigs are popular because they are accessible, healthier than conventional cigarettes and more aesthetically pleasing, 33,39 but had some concerns about the possible toxicity and the future legal status of the devices. 40…”
Section: The Relationship Between Smoking and Vapingmentioning
confidence: 98%
“…Hospitalised tobacco smokers expect fewer negative and positive outcomes from e-cigs versus conventional cigarettes, which suggests that e-cigs might be a viable, though imperfect, substitute to conventional cigarettes. 38 Vapers stated that e-cigs are popular because they are accessible, healthier than conventional cigarettes and more aesthetically pleasing, 33,39 but had some concerns about the possible toxicity and the future legal status of the devices. 40…”
Section: The Relationship Between Smoking and Vapingmentioning
confidence: 98%
“…15 Marketing of e-cigarettes has been directed at the young adults and children according to the United States Food and Drug Administration documents. 2 Electronic cigarette manufacturers advertise heavily through social networking systems and avoid using the word cigarette because of its negative connotations. Teenagers may deny using electronic cigarettes, but vape, for example, on a nicotine-containing, flavored hookah pen.…”
Section: Youth Is the Growing Marketmentioning
confidence: 99%
“…By 2007, electronic cigarettes had reached Europe and North America, and sales soon skyrocketed. 2 In 2009, only 16% of Americans were aware of electronic cigarettes, but by 2010, 32% were aware of them.…”
Section: Introductionmentioning
confidence: 99%
“…In 1 study conducted in Birmingham, Alabama in 2012–2013, hospitalized smokers reported that they expected e-cigarettes to be less effective at relieving negative affect and satisfying nicotine cravings and that the taste would not be as pleasant as combustible cigarettes (Hendricks et al, 2015). Rigotti and colleagues (2015) examined past 30-day e-cigarette use among 4660 smokers enrolled in a consortium of hospital-based cessation trials (CHART) from 2010 to 2013.…”
mentioning
confidence: 99%
“…Other studies included patients who agreed to participate in a research study (eg, Harrington et al, 2014; Baumann et al, 2015) or excluded tobacco-using patients who had never heard of e-cigarettes (eg, Hendricks et al, 2015). Consequently, these results may not generalize to all hospitalized smokers.…”
mentioning
confidence: 99%